JUSTICE IN INTELLECTUAL PROPERTY - Nelson, Dustin S. (Ethics, Politics & Society, 2023)
Intellectual property (IP) rights represent an anomaly within a free market economic system. IP rights, that is, necessarily constrain the actions of individuals within the market. In response to this anomaly, IP scholars have offered various justifications for the application of such supposed constraints within a free market economy. Chief among these justifications is the widespread appeal to utilitarianism via incentivization. Yet, it is not exactly clear that this incentivization is actually producing the benefits required for the utilitarian justification. Rather than abandoning the IP system, however, some have simply suggested an alternative justification. These scholars argue that IP rights are actual, moral rights that deserve protection as moral rights. Further, scholars argue that any distributional inequality generated by the IP system are nonetheless justified under Rawls’s theory of justice. I argue, however, that Rawls’s theory of justice cannot “justify” a selective, IP regime.